Workshop Digital Teacherpreneur Pengembangan Ketrampilan Digital dan Kewirausahaan Guru Provinsi Riau - Annisa Mardatillah; Ria Darmasari; Mimelientesa Irman (CANANG: Jurnal Pengabdian Masyarakat, 2026)
The Digital Teacherpreneur Workshop was initiated to address the suboptimal use of digital technology by teachers as a creative economic opportunity. This activity aims to improve teachers' digital skills, managerial abilities, and entrepreneurial mindset through ongoing training and mentoring. The method used was participatory training, with pre- and post-test evaluations of 21 participants across six indicators: digital literacy, content creativity, platform management, digital marketing, managerial skills, and entrepreneurial mindset. The results showed significant improvements in all indicators. The most prominent improvements were seen in digital content creativity and entrepreneurial mindset, indicating a transformation not only in technical aspects but also in participants' mindsets. Furthermore, teachers' abilities to manage digital platforms and implement marketing strategies have also developed significantly, thereby supporting the potential monetization of technology-based educational products. The workshop concluded that it was effective in holistically improving teachers' digitalpreneur competencies. This program not only strengthens individual capacity but also opens up additional income opportunities and encourages the creation of an innovative, productive, and sustainable education ecosystem in the digital era